Trajectories of symptoms of depression, distress, and resilience in healthcare workers during the COVID-19 pandemic and toward its end in Czechia - Brennan Kearns, Pavla; Csajbók, Zsófia; Janoušková, Miroslava; Kučera, Matěj; Novák, David; Fryčová, Barbora; Kuklová, Marie; Pekara, Jaroslav; Šeblová, Jana; Seblova, Dominika (European psychiatry, 2024)
The mental health of healthcare workers (HCWs) may have improved after the COVID-19 pandemic. We aimed to model the trajectories of psychological distress, depressive symptoms, and resilience during the COVID-19 pandemic and toward its end in HCWs in Czechia and investigate, which COVID-19 work stressors were associated with these trajectories. The study included 322 HCWs from the Czech arm of the international HEROES Study who participated in an online questionnaire in two waves during the pandemic and one wave toward its end. Growth mixture modeling identified trajectory patterns of depressive symptoms (measured with Patient Health Questionnaire), distress (General Health Questionnaire), and resilience (Brief Resilience Scale). Logistic regression was applied to estimate the association of COVID-19 stressors with mental health trajectories, adjusting for baseline characteristics. Trajectory classes revealed both high and low depressive symptoms (high in 61% of participants), distress (high in 82% of participants), and resilience (low in 32% of participants). Depressive symptoms and distress trajectories demonstrated the same shape, first increasing during the pandemic and decreasing toward its end, while resilience remained constant. Exposure to COVID-19 stressors, in particular, the experience of stigmatization, discrimination, and violence, was associated with high depressive symptoms and distress trajectories, but not with resilience. Interventions provided to HCWs during crises such as pandemic should target distress and depressive symptoms and need to address stigmatization, discrimination, and violence.